EDUKASI DAN PELATIHAN PENILAIAN STATUS GIZI PADA REMAJA DI SMP YARI KOTA PADANG - Ade Teti Vani; Irwan Triansyah; Nadia Dewi; Dessy Abdullah; Mutiara Annisa (Yayasan Nusantara Hasana Berdikari, 2023)
Motivation/Background: Adolescents experience triple burden malnutrition; malnutrition, overweight, micronutrient deficiencies with anemia. Body Mass Index (BMI) assessment is used as a recommendation for nutritional status indicators in adolescents. BMI assessments are practical and easy to perform so that adolescents can independently evaluate their nutritional status. The purpose of this community service activity is to provide education on the importance of monitoring and evaluating nutritional status in adolescents and train adolescents to calculate and self-assess nutritional status. Method: The method of devotion used consists of 3 stages. The first stage is the provision of counseling on nutritional status, how to measure nutritional status and nutritional status assessment. The second stage is to train students to measure and measure their nutritional status. The last stage is education on the results of students' nutritional status in order to achieve normal nutritional status. Results: The result of devotion is an average body weight of 51.51±12.06 kg. The average height is 157±5.56 cm. Almost nutritional status of adolescents found by normoweight. However, cases of underweight and obese were still found in YARI Junior High School students. Conclusions: The conclusion of this service activity is that most of the students of YARI school junior high school have good nutritional status, but there are still cases of triple burden malnutrition that require holistic treatment.